Release Kinetics and Antibacterial Efficacy of Microporous β-TCP Coatings. (25th November 2013) - Seidenstuecker, Michael; Mrestani, Yahya; Neubert, Reinhard H. H.; Bernstein, Anke; Mayr, Hermann O.
Abstract : Purpose . The aim of this study was to impregnate microporous β -TCP scaffolds with different antibiotic solutions and to determine their release behavior. Materials and Methods . We impregnated a β -TCP scaffold with antibiotics by using three methods: drop, dip, and stream coating with 120 mg/mL of antibiotic solution. After drying for 72 h at 37°C, 2 mL of distilled water was added to the antibiotic-coated plugs and incubated at 37°C. After defined time points (1, 2, 3, 6, 9, and 14 days), the liquid was completely replaced. The extracted liquid was analyzed by capillary zone electrophoresis and the Kirby Bauer disc diffusion test. For statistical analysis, we calculated a mean and standard deviation and carried out an analysis of variance using ANOVA. Results . The VAN and CLI release from the β -TCP scaffolds was rapid, occurring within 24 h with 89 ± 0.8% VAN and 90.4 ± 1.5% CLI regardless of the type of insulation. After six days, the VAN and CLI were completely released. All samples taken at later time points had a VAN or CLI concentration below the detection limit of 4 µg/mL. The released amounts of VAN and CLI within the first three days revealed antimicrobial activity.